Gill transcriptome profiling reveals adaptation to brackish water in a selectively bred hybrid tilapia (Oreochromis niloticus x O. aureus) strain - Xiaofei Yu; July B. Ariñez; Priadi Setyawan; Zhitian Wu; Muhammad Hunaina Fariduddin Aththar; Mark Camara; Yang Fang; Martien A.M. Groenen; Hans Komen; John W.M. Bastiaansen; Hendrik-Jan Megens (Aquaculture Reports)
Salinity tolerance varies among tilapia species and salinity-tolerant strains can be produced through selective breeding. In Indonesia, breeding programs have produced Sukamandi, a tilapia strain with improved growth in brackish water. Here, we investigated the salinity tolerance of this strain by performing a transcriptomic analysis using offsprings from the fifth generation of a breeding population. Based on estimated breeding values, we formed three genetic groups: brackish water-specialized tilapia, freshwater-specialized tilapia, and generalist tilapia. Progeny (average weight of ∼100 g) from these groups were stocked in both brackish water (25 ppt) and freshwater (0 ppt) tanks for short (3 days) and long term (28 days) exposure periods. Our results showed that brackish water reared fish had higher Na+ and Cl- concentrations in blood plasma while haematocrit levels were not affected by salinity across all genetic groups. For Na+/K+-ATPase concentration, the interaction between genetic groups and salinity environment was significant. Ion homeostasis and sodium-potassium-chloride symporter activities were key processes exhibited by brackish water relative to freshwater fish. Short-term brackish water acclimation uniquely triggered the activation of prolactin receptor activity and calcium signaling pathway, whereas long-term exposure was specifically associated with immune responses, DNA damage, and apoptosis. Upon checking the Differentially Expressed Genes within osmoregulation-related terms common in all tested groups, six candidate responsive genes to osmotic stress were identified: aqp3a, atp1a1b, slc12a2, slc45a3, slc12a10.1 and slc1210.3. Overall, this study sheds light into the genetic factors influencing the adaptation of Sukamandi strain to salinity stress and identify candidate genes that can be potentially used as markers for salinity tolerance breeding in the future.